Krisis Perencanaan Transportasi Kota - Harun al-Rasyid S Lubis; Rudy Hermawan Karsaman (Journal of Regional and City Planning, 1997)
In Indonesia, the study on the correlation between land-use and transportation was started 21 cyears ago following similiar studies conducted by developed countries 43 years ago. The main purpose of these studies was to prepare an efficient transportation plan for a city or region in order to facilitate the increase in the traffic as the result of the growth of social-economic activities in the city in the future Due to inconsistency between plan and reality in the implementation phase, in the developed countries critiques on the failures of these studies emerged in the middle of 1970"²s, at the time when the methods and technologies were being imported by developed countries, and in Indonesia, there has been a crisis in urban transportation planning. This article tries to look back at history of the implementation of similar studies in large cities of Indonesia and in the neighboring countries. Some weaknesses of the studies and the modeling will be identified. At the end, the article discusses the weaknesses in the implementation phase of urban transportation plan in Indonesia and alternative policies for the future.